2017
DOI: 10.1111/radm.12258
|View full text |Cite
|
Sign up to set email alerts
|

Creating shareholder value via collaborative innovation: the role of industry and resource alignment in knowledge exploration

Abstract: Collaborative innovation provides firms with a privileged opportunity to perform exploration in an externally oriented mode. The central challenges in exploration via collaborative innovation lie in the selection of relevant partners and in gaining access to potentially valuable external knowledge that the focal firm lacks. This article focuses on two aspects of inter-organizational alignment that affect knowledge differences and may thus help explaining the shareholder value implications arising from collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 126 publications
0
25
0
1
Order By: Relevance
“…The Republic of Korea also acts as a major consumer of Russian oil in the region, where more than 5% of exports go. Due to the fact that the vast majority of oil refineries in the country are included in the structure of vertically integrated companies, they are provided with their own raw materials [1][2][3][4][5][6]. In this regard, the import of crude oil into Russia is insignificant; he comes from Kazakhstan, mainly to the Orenburg region.…”
Section: Resultsmentioning
confidence: 99%
“…The Republic of Korea also acts as a major consumer of Russian oil in the region, where more than 5% of exports go. Due to the fact that the vast majority of oil refineries in the country are included in the structure of vertically integrated companies, they are provided with their own raw materials [1][2][3][4][5][6]. In this regard, the import of crude oil into Russia is insignificant; he comes from Kazakhstan, mainly to the Orenburg region.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous research on open innovation has mainly focused on collaborative inventing; currently, open innovation requires collaboration among distributed but interdependent actors who rely on each other"s capabilities for value creation and capture. Many study perspectives currently offer value perspective on open innovation (Chesbrough et al, 2018;Eggert et al, 2018;Heil & Bornemann, 2018). We hypothesize a role of continuous cooperation in supply chainssupply side -both early and in the experimental sense, in the processes of creating innovative processes concerning products and business models.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…rough empirical research, Heil and Bornemann demonstrated that the integration of R&D resources would affect the investor's evaluation on future cooperative performance [5].…”
Section: Multiplayer Collaborative Innovationmentioning
confidence: 99%